Evaluation of Patterns of Comorbidities Among Patients Admitted for Elective and Emergency Surgery for Avoiding Medico-Legal Conflict - Sharma , M; Choudhury, C; Sharma, Narayan C; Das, A; Gogoi , A; Rajbangshi , MC; Mahanta, P (Journal of Indian Academy of Forensic Medicine, 2024)
Comorbidity, defined as several diseases in a patient connected through proven pathogenic mechanisms, necessitates identifying the diseases requiring primary and subsequent treatment. The comorbid condition may invite unnecessary conflict while treating surgically, which needs special pre and post-operative attention. The present study aims to evaluate the prevalence and the patterns of comorbidities among patients admitted for elective and emergency surgery to avoid medico-legal conflict. The present hospital-based prospective observational study was undertaken at the Department of Surgery, Gauhati Medical College and Hospital (GMCH), Guwahati, from June 1, 2018, to May 31, 2019. All patients admitted for elective or emergency surgery, with neither or at most two comorbid conditions fulfilling the inclusion-exclusion criteria, were included in the study. The data were analysed using SPSS V 21. A total of 309 cases were selected for the study. Most of the cases belonged to the age group 20-49 years, males (73%) and belonged to lower socioeconomic status (63.7%). Among females, chronic calculous cholecystitis (62.7%), while among males, hollow viscus perforation (35.4%) and unilateral and obstructed inguinal hernia (23.0%) were mainly reported. Almost 53% of the cases had comorbidity. Anaemia (18.1%), hypertension (16.9%) and type 2 diabetes mellitus (12.0%) mainly were reported comorbidities among females, while among males, type 2 diabetes mellitus (15.0%) and chronic obstructive pulmonary diseases (11.5%) were the most common. Comorbidities were prevalent among the study group. The adult age group is more prone to having one or more comorbidities. Controlling comorbidities in the preoperative phase is crucial in surgery for a better outcome.